Aplikasi Polimerase Chain Reaction (PCR) dalam Menjamin Kehalalan dan Keamanan pada Produk Bakso Daging Sapi - Laksono, Tomi (Maliki Interdisciplinary Journal, 2025)
Halal and food safety are two very important aspects in the food industry, especially in Indonesia, where the majority of the population is Muslim. As one of the popular foods in Indonesia, beef meatballs face challenges related to the potential contamination of non-halal ingredients, such as pork, and dangerous pathogenic microbes that can endanger the health of consumers. To ensure halal and food safety, molecular biology technology, especially Polymerase Chain Reaction (PCR), offers an effective solution. This study aims to explore the application of PCR in detecting contamination of non-halal ingredients and pathogenic microbes in beef meatball products. PCR has high sensitivity in detecting DNA of haram ingredients, such as pork, as well as pathogenic microorganisms such as Salmonella and Escherichia coli, which can cause food poisoning. The advantage of PCR lies in its ability to provide fast and accurate detection results, even in very small sample sizes, compared to conventional methods. The application of PCR technology in the meatball industry can improve the quality of halal and product safety, maintain consumer health, and strengthen market confidence in the products sold. Thus, PCR is a very important tool in ensuring that meatball products meet high halal and food safety standards.